The specificity of the individual professional practice of midwives with regard to home births. Analysis of the ‘relationship field’ - Nowakowska, Luiza (Polish Journal of Public Health, 2018)
Introduction. By virtue of the Act of 5 July 1996 on the occupation of nurses and midwives, a midwife in Poland has full professional autonomy. The Act does not forbid conduct of individual practice outside of a hospital.Aim. The purpose of the article is to present practical execution of individual practice of assisting during home birth with regard to relations between the midwife and the woman giving birth.Materials and methods. The issues presented in the article are a part of broader research concerning home births in Poland. The research was commenced in 2014 and finalized in 2018. The analysis concerned statements of women who decided not to give birth in a hospital. I obtained the empirical material through in-depth interviews and I referred to data existing in the form of e.g. blog entries. Finally, I collected 40 descriptions of home births. They underwent a qualitative analysis with the use of the grounded theory methodology and the social world theory.Results. The outcome of the research is a multifaceted “sociological portrait” of the world of women, which implement an alternative to the hospital birth scenario. In the article, I limit myself to the presentation of mechanisms of transformation of midwife-birthing woman relations from professionally neutral to emotionally involved: mutual appreciation, balancing of positions, comprehensive qualification, systematic maintenance of relations, and feminization of birth. I also presented the principles of cooperation with the birthing woman during home birth: constant and imperceptible presence, following a woman, patient accompaniment, support, animation of bonds, and respect for the ceremony. The whole discussion depicts the special character of the individual practice of midwives with regard to the field of relations.Conclusion. Reference to childbirth experiences allowed for identifying potential expectations of women planning to have children towards the midwife’s profession, as well as the possible paths of professional development of representatives of this profession, especially in the face of the growing awareness and autonomy of people using health care services. These issues may also be treated as an element of a broader discussion on the shape of an optimum pre- and post-natal care.